x2−5x+6=0 by formula method
Answers
Answered by
7
HERE IS YOUR ANSWER...⬇⬇
=====================================
➡
![Formula \: \: Method \: : - \\ \\ \boxed{ x = \frac{ - b± \sqrt{b {}^{2} - 4ac } }{2a} } Formula \: \: Method \: : - \\ \\ \boxed{ x = \frac{ - b± \sqrt{b {}^{2} - 4ac } }{2a} }](https://tex.z-dn.net/?f=+Formula+%5C%3A+%5C%3A+Method+%5C%3A+%3A+-+%5C%5C+%5C%5C+%5Cboxed%7B+x+%3D+%5Cfrac%7B+-+b%C2%B1+%5Csqrt%7Bb+%7B%7D%5E%7B2%7D+-+4ac+%7D+%7D%7B2a%7D+%7D)
![Now, \\ \\ Given \: : x {}^{2} - 5x + 6 = 0 \\ \\ Here, \\ \\ a = 1 \\ \\ b = - 5 \\ \\ c = 6 Now, \\ \\ Given \: : x {}^{2} - 5x + 6 = 0 \\ \\ Here, \\ \\ a = 1 \\ \\ b = - 5 \\ \\ c = 6](https://tex.z-dn.net/?f=Now%2C+%5C%5C+%5C%5C+Given+%5C%3A+%3A+x+%7B%7D%5E%7B2%7D+-+5x+%2B+6+%3D+0+%5C%5C+%5C%5C+Here%2C+%5C%5C+%5C%5C+a+%3D+1+%5C%5C+%5C%5C+b+%3D+-+5+%5C%5C+%5C%5C+c+%3D+6)
![Putting \: \: the \: \: values \: \: of \: \: a\: , \: b \:\: and \: \: c \: \: \\ in \: \: the \: \: formula \: \: method \: :- Putting \: \: the \: \: values \: \: of \: \: a\: , \: b \:\: and \: \: c \: \: \\ in \: \: the \: \: formula \: \: method \: :-](https://tex.z-dn.net/?f=Putting+%5C%3A+%5C%3A+the+%5C%3A+%5C%3A+values+%5C%3A+%5C%3A+of+%5C%3A+%5C%3A+a%5C%3A+%2C+%5C%3A+b+%5C%3A%5C%3A+and+%5C%3A+%5C%3A+c+%5C%3A+%5C%3A+%5C%5C+in+%5C%3A+%5C%3A+the+%5C%3A+%5C%3A+formula+%5C%3A+%5C%3A+method+%5C%3A+%3A-+)
![x = \frac{ - b± \sqrt{b {}^{2} - 4ac } }{2a} \\ \\ = \frac{ - ( - 5)± \sqrt{( - 5) {}^{2} - 4 \times 1 \times 6} }{2 \times 1} \\ \\ = \frac{5± \sqrt{25 - 24} }{2} \\ \\ = \frac{5± \sqrt{1} }{2} \\ \\ = \frac{5±1}{2} x = \frac{ - b± \sqrt{b {}^{2} - 4ac } }{2a} \\ \\ = \frac{ - ( - 5)± \sqrt{( - 5) {}^{2} - 4 \times 1 \times 6} }{2 \times 1} \\ \\ = \frac{5± \sqrt{25 - 24} }{2} \\ \\ = \frac{5± \sqrt{1} }{2} \\ \\ = \frac{5±1}{2}](https://tex.z-dn.net/?f=x+%3D+%5Cfrac%7B+-+b%C2%B1+%5Csqrt%7Bb+%7B%7D%5E%7B2%7D+-+4ac+%7D+%7D%7B2a%7D+%5C%5C+%5C%5C+%3D+%5Cfrac%7B+-+%28+-+5%29%C2%B1+%5Csqrt%7B%28+-+5%29+%7B%7D%5E%7B2%7D+-+4+%5Ctimes+1+%5Ctimes+6%7D+%7D%7B2+%5Ctimes+1%7D+%5C%5C+%5C%5C+%3D+%5Cfrac%7B5%C2%B1+%5Csqrt%7B25+-+24%7D+%7D%7B2%7D+%5C%5C+%5C%5C+%3D+%5Cfrac%7B5%C2%B1+%5Csqrt%7B1%7D+%7D%7B2%7D+%5C%5C+%5C%5C+%3D+%5Cfrac%7B5%C2%B11%7D%7B2%7D+)
![Therefore, \\ \\ x = \frac{5±1}{2} \\ \\ So, \\ \\ x = \frac{5 +1 }{2} \\ \\ = > x = \frac{6}{2} \\ \\ = > x = 3 \\ \\ Or , \\ \\ x = \frac{5 - 1}{2} \\ \\ = > x = \frac{4}{2} \\ \\ = > x = 2 Therefore, \\ \\ x = \frac{5±1}{2} \\ \\ So, \\ \\ x = \frac{5 +1 }{2} \\ \\ = > x = \frac{6}{2} \\ \\ = > x = 3 \\ \\ Or , \\ \\ x = \frac{5 - 1}{2} \\ \\ = > x = \frac{4}{2} \\ \\ = > x = 2](https://tex.z-dn.net/?f=Therefore%2C+%5C%5C+%5C%5C+x+%3D+%5Cfrac%7B5%C2%B11%7D%7B2%7D+%5C%5C+%5C%5C+So%2C+%5C%5C+%5C%5C+x+%3D+%5Cfrac%7B5+%2B1+%7D%7B2%7D+%5C%5C+%5C%5C+%3D+%26gt%3B+x+%3D+%5Cfrac%7B6%7D%7B2%7D+%5C%5C+%5C%5C+%3D+%26gt%3B+x+%3D+3+%5C%5C+%5C%5C+Or+%2C+%5C%5C+%5C%5C+x+%3D+%5Cfrac%7B5+-+1%7D%7B2%7D+%5C%5C+%5C%5C+%3D+%26gt%3B+x+%3D+%5Cfrac%7B4%7D%7B2%7D+%5C%5C+%5C%5C+%3D+%26gt%3B+x+%3D+2)
➡ ![\boxed{ x = 3 \: , \: x = 2 } \boxed{ x = 3 \: , \: x = 2 }](https://tex.z-dn.net/?f=%5Cboxed%7B+x+%3D+3+%5C%3A+%2C+%5C%3A+x+%3D+2+%7D)
___________________________________
✝✝…HOPE…IT…HELPS…YOU…✝✝
=====================================
___________________________________
✝✝…HOPE…IT…HELPS…YOU…✝✝
Answered by
3
HOPE IT HELPS YOU
MARK ME AS BRILLIANT
Attachments:
![](https://hi-static.z-dn.net/files/d5d/79d594033ce1bd291676c27f4c9d40ef.jpg)
Similar questions